2021
DOI: 10.3390/pr9101738
|View full text |Cite
|
Sign up to set email alerts
|

Drying Characteristics and Quality Attributes Affected by a Fluidized-Bed Drying Assisted with Swirling Compressed-Air for Preparing Instant Red Jasmine Rice

Abstract: A new process for the production of instant red jasmine rice was investigated using fluidized bed drying with the aid of swirling compressed air. Drying characteristics were evaluated using the operating parameters of fluidizing air temperature (90–120 °C) and pressure of swirling compressed air (4–6 bar). Appropriate air pressure was determined based on the highest value of model parameters from the semi-empirical Page equation and effective diffusivity. Influences of supply time of swirling compressed air (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Moreover, Figure 2 also showed that increasing drying temperatures speed up the sample to reach its moisture equilibrium. A similar result was presented by Chupawa et al [14] when dried red Jasmine rice using a fluidized-bed-dryer. Higher air temperature supplies more energy that can be used to evaporate water.…”
Section: Moisture Content Of Coarse Palm Sap Sugar During Drying Processsupporting
confidence: 85%
“…Moreover, Figure 2 also showed that increasing drying temperatures speed up the sample to reach its moisture equilibrium. A similar result was presented by Chupawa et al [14] when dried red Jasmine rice using a fluidized-bed-dryer. Higher air temperature supplies more energy that can be used to evaporate water.…”
Section: Moisture Content Of Coarse Palm Sap Sugar During Drying Processsupporting
confidence: 85%
“… where MR LW denotes moisture ratio using the Lewis model, MR HP denotes moisture ratio using the Henderson–Pabis model, a denotes model constant, k denotes rate constant, and t is drying time in minutes. The rate constant (k) represents drying performance, with a high value representing a fast-drying rate [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Also, due to the poor heat transfer rate as the sublimation front goes from the exterior to the interior of the frozen ginger being dried, FD takes longer than OD and SFBD (Sivakumar et al, 2016). The study reported by Chupawa et al (2021), stated that the hydrodynamics of gas-solid phases are directly linked to the heat transfer phenomena, and turbulence can improve the flow homogeneity and mixing efficiency.…”
Section: Moisture Ratiomentioning
confidence: 99%